Deformation Characteristics of Ultrahigh-Strength Concrete under Unrestrained and Restrained States - Joo-Ha Lee; Kwang-Mo Lim; Doo-Yeol Yoo; Nam-Hyoung Lim (Advances in Materials Science and Engineering)
As structures like skyscrapers and long-span bridges become larger, the demand for higher strength of concrete is increasing. However, research on ultrahigh-strength concrete (UHSC) is still in its infancy. In particular, UHSC is known to have a considerably higher level of autogenous shrinkage than normal strength concrete (NSC), and the possibility of cracking at an early age is very high. Therefore, in this study, shrinkage and cracking behavior of high-strength concrete (HSC), very-high-strength concrete (VHSC), and UHSC were evaluated through unrestrained shrinkage test and restrained shrinkage test (ring test). The primary experimental variables are the compressive strength level according to the water-to-binder ratio (W/B), fly ash content, and concrete specimen thickness. The experimental results demonstrated that the drying shrinkage decreased as the W/B ratio and the fly ash replacement ratio increased, and the restraint cracks appeared to be the earliest and most brittle in the UHSC with the smallest W/B. Increased concrete thickness and incorporation of fly ash were observed to inhibit crack initiation effectively.